Pengaruh Larutan Ekstrak Siwak (Salvadora persica) Terhadap Streptococcus mutans: Studi In Vitro dan In Vivo - Oedijani Santoso; Aini Pramoda Wardani; Nila Kusumasari (MEDIA MEDIKA INDONESIANA, 2012)
The influence of Siwak (Salvadora persica) extract solution on Streptococcus mutans, in vitro and in vivo studyBackground: Streptococcus mutans is the primary cause of dental caries. Siwak (Salvadora persica) may improve oral health with antibacterial effects and prevent decreasing of salivary pH. The aim of this research was to know the influence of siwak extract solution on the growth of S.mutans (in vitro) and salivary pH (in vivo).Method: I. Laboratory experimental with the post test only control group design using S.mutans as samples. The intervention groups were given siwak extract solution at various concentrations 3.1%, 6.2%, 12.5%, 25%, 50%, and 100%. The data was obtained by visually observing the growth of S.mutans colonies. Statistical test used the Kruskal-Wallis test followed by Mann-Whitney test. II. Clinical trial with the post test only control group design. 74 samples divided randomly into two groups they were control and test group. The test group rinse the mouth with 25% the siwak extract solution. Salivary pH was measured using Hanna digital pH meter with 0,1 sensitivity. The data analyzed by Shapiro-Wilk test continued by Mann-Whitney test.Result: I. Test group with concentrations of 50% and 100% were no visible growth of S.mutans, however another group still appeared the growth of S.mutans. Kruskal-Wallis test revealed a significant difference (p=0.003), Mann-Whitney test which also showed a significant difference (p=0.025). II. There was significant different on salivary pH at the test group compared to the control group (p<0.05).Conclusion: I. Siwak extract solution can inhibit the growth of S.mutans, concentration of 50% is the lowest concentration that effective to inhibit the growth of S. mutans. II. Giving the solution of siwak extract 25% can increase salivary pH significantly.Keywords: Siwak extract solution, S. mutans, salivary pH ABSTRAKLatar belakang: Streptococcus mutans merupakan penyebab utama karies. Siwak (Salvadora persica) mampu meningkatkan kesehatan mulut dengan efek antibakterial dan mencegah penurunan pH saliva. Tujuan penelitian untuk mengetahui pengaruh larutan ekstrak siwak terhadap pertumbuhan S.mutans (in vitro) dan pH saliva (in vivo).Metode: I. Eksperimental laboratorik rancangan the post test only control group design, S.mutans sebagai sampel. Perlakuan diberikan larutan ekstrak siwak konsentrasi 100%, 50%, 25%, 12,5%, 6,2%, dan 3,1%, penilaian pertumbuhan koloni S.mutans secara visual. Analisis data dengan uji Kruskal-Wallis dilanjutkan dengan uji Mann-Whitney. II. Uji klinis rancangan the post test only control group design. Sampel 74 orang, secara random dibagi dua kelompok kontrol dan perlakuan diberikan larutan ekstrak siwak 25% untuk kumur. pH saliva diukur dengan pH meter digital Hanna dengan sensitivitas 0,1. Analisis data dengan uji Shapiro- Wilk dilanjutkan dengan uji Mann-Whitney.Hasil: I. Kelompok perlakuan konsentrasi 50% dan 100% tidak tampak adanya pertumbuhan S. mutans, namun kelompok yang lain masih tampak adanya pertumbuhan S. mutans. Uji Kruskal-Wallis didapatkan perbedaan signifikan (p=0,003), uji Mann-Whitney juga didapatkan perbedaan signifikan (p=0,025). II. Terdapat perbedaan bermakna pada pH saliva antara kelompok perlakuan dibanding kontrol (p<0,05).Simpulan: I. Larutan ekstrak siwak dapat menghambat pertumbuhan S. mutans, konsentrasi 50% adalah konsentrasi terendah yang efektif menghambat pertumbuhan S. mutans. II. Kumur larutan ekstrak siwak 25% dapat meningkatkan pH saliva secara bermakna.